Measuring the Rule of Law: A Comparison of Indicators. Issue 1 (3rd February 2016) - Versteeg, Mila; Ginsburg, Tom
Abstract : The rule of law era has given rise to multiple indicators purporting to measure the concept. This article compares four major indicators of the rule of law and shows that their approaches to conceptualization and measurement differ. Given their disparate conceptualizations and measurement strategies, one might expect a weak correlation between them. Strikingly, however, all four indicators are highly correlated with each other (with the pair‐wise correlations between three of them exceeding 0.95). They are also correlated with the widely used measure of corruption. This suggests that the indicators might capture a more encompassing concept, like impartial administration. The article critiques the rule of law measurement enterprise as insufficiently linked to the underlying normative concept. It points to the reliance on expert perceptions and information constraints as a possible cause for the convergence. It concludes that measurement strategy, rather than differences in conceptualization, explains the convergence between the indicators.